The Use of Wireless E-Mail to Improve Healthcare Team Communication - O'Connor, Chris (American Medical Informatics Association, 2009)
OBJECTIVE: To assess the impact of using wireless e-mail for clinical communication in an intensive care unit (ICU). DESIGN: The authors implemented push wireless e-mail over a GSM cellular network in a 26-bed ICU during a 6-month study period. Daytime ICU staff (intensivists, nurses, respiratory therapists, pharmacists, clerical staff, and ICU leadership) used handheld devices (BlackBerry, Research in Motion, Waterloo, ON) without dedicated training. The authors recorded e-mail volume and used standard methods to develop a self-administered survey of ICU staff to measure wireless e-mail impact. MEASUREMENTS: The survey assessed perceived impact of wireless e-mail on communication, team relationships, staff satisfaction and patient care. Answers were recorded on a 7-point Likert scale; favorable responses were categorized as Likert responses 5, 6, and 7. RESULTS: Staff sent 5.2 (1.9) and received 8.9 (2.1) messages (mean [SD]) per day during 5 months of the 6-month study period; usage decreased after study completion. Most (106/125 [85%]) staff completed the questionnaire. The majority reported that wireless e-mail improved speed (92%) and reliability (92%) of communication, improved coordination of ICU team members (88%), reduced staff frustration (75%), and resulted in faster (90%) and safer (75%) patient care; Likert responses were significantly different from neutral (p < 0.001 for all). Staff infrequently (18%) reported negative effects on communication. There were no reports of radiofrequency interference with medical devices. CONCLUSIONS: Interdisciplinary ICU staff perceived wireless e-mail to improve communication, team relationships, staff satisfaction, and patient care. Further research should address the impact of wireless e-mail on efficiency and timeliness of staff workflow and clinical outcomes.